Lessonslearntand perspectives from a global effort to support the deployment of underutilized species, with special reference to documentation of knowledge and information - Hoeschle-Zeledon, Irmgard (Bioversity International, 2012)
This paper focuses on the role of the Global Facilitation Unit for Underutilized Species in the promotion and facilitation of the sustainable deployment of underutilized plant species to increase the security of food and nutrition and alleviate poverty among poor rural and urban communities.